VETERINARY AND SANITARY ASPECTS AND TECHNOLOGIES FOR PROCESSING KERATIN AND COLLAGEN CONTAINING WASTE FORMED IN SLAUGHTER POINTS OF RURAL SETTLEMENTS (ON EXAMPLE OF HORSE - HOOVED) - Montayeva, N. S. (Ғылым және білім №1, 2020)
The article presents the results of a study on the analysis of rational processing technologies for keratin and collagen-containing meat processing wastes regarding the receipt of demanded products. It has been established that one of the effective ways of processing keratin and collagen-containing waste is to obtain protein feed additives based on various technological processes. The problems of utilization and processing of keratin and collagen-containing waste in existing slaughter shops located in rural areas, consisting in the absence of special facilities for storing and processing these wastes, are revealed. As a result, these wastes are disposed of in landfills without complying with veterinary and sanitary requirements and recommendations, which can lead to the propagation of harmful viruses for human and animal health. To solve this problem, a technological scheme has been developed for processing collagen and keratin-containing raw materials formed in such slaughterhouses with the development of specific veterinary and sanitary requirements and recommendations based on the example of horns and hooves. In laboratory conditions, according to the model of the developed technological scheme, scientific and experimental work was carried out to obtain a protein product by the method of hydrolysis of horns and hooves. As a result, experimental samples of a protein product and a liquid protein concentrate with high emulsifying ability were obtained. - the resulting feed additive contains at least 70% protein and 6% fat with 9% moisture. The product yield was 65-70% by weight of fresh horned hoofed raw materials. РЕЗЮМЕ В статье представлены результаты исследования по анализу рациональных технологии переработки кератин и коллагенсодаржащих отходов мясопереработки касательно получения востребованных продуктов. Установлено, что одним из эффективных путей переработки кератин и коллагенсодержащих отходов является получение белковых кормовых добавок на основе различных технологических процессов. Выявлены проблемы утилизации и переработки кератин и коллагенсодержащих отходов в существующих убойных цехах расположенных в сельских населенных пунктах, заключающиеся в отсутствии специальных помещений для хранения и переработки указанных отходов. В результате эти отходы вывозится на свалки без соблюдения ветеринарно-санитарных требований и рекомендации, что могут привести размножению вредных вирусов для здоровья людей и животных. Для решения данной проблемы разработана технологическая схема переработки коллаген и кератинсодержащего сырья, образующихся в подобных убойных пунктах с разработкой конкретных ветеринарно-санитарных требований и рекомендаций на примере рогов и копыт. В лабораторных условиях по модели разработанной технологической схемы проведены научно-экспериментальные работы по получению белкового продукта по методу гидролиза рогов и копыт. В результате получены опытные образцы белкового продукта и жидкого белкового концентрата обладающего высокой эмульгирующей способностью. Полученная кормовая добавка содержит не менее 70% протеина и 6% жира при 9% влаги. Выход продукта составляло 65-70% от массы свежего рогокопытного сырья.
Keywords: журнал кксон -- рк -- научный журнал -- периодическое издание -- отечественное издание -- размножение вредных вирусов -- ветеринарно-санитарные требования -- кормовые добавки -- белковые продукты -- кератин -- keratin -- collagen -- veterinary and sanitary aspects -- slaughterhouse -- hydrolysis; рк; научный журнал; периодическое издание; отечественное издание; размножение вредных вирусов; ветеринарно-санитарные требования; кормовые добавки; белковые продукты; кератин; keratin; collagen; veterinary and sanitary aspects; slaughterhouse; hydrolysis